1974
DOI: 10.1590/s0034-89101974000200008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de enteroparasitas na população urbana do 2.° subdistrito de Botucatu, SP (Brasil)<A NAME="top1"></A>

Abstract: RSPU-B/218OLIVEIRA, M. R. et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
3

Year Published

1976
1976
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
1
1
3
Order By: Relevance
“…The prevalence of G. duodenalis in the elderly was higher than observed in previous studies 1,2,3,20,23 and lower than observed in other studies 12,14,27 . The difference in the results can be associated with the number of samples taken, methodology, environmental differences and The prevalence observed for Cryptosporidium spp.…”
Section: Discussioncontrasting
confidence: 69%
“…The prevalence of G. duodenalis in the elderly was higher than observed in previous studies 1,2,3,20,23 and lower than observed in other studies 12,14,27 . The difference in the results can be associated with the number of samples taken, methodology, environmental differences and The prevalence observed for Cryptosporidium spp.…”
Section: Discussioncontrasting
confidence: 69%
“…There are few studies available on the prevalence of enteroparasites in our region at southeast Brazil. The reported data on the prevalence of enteroparasites in Botucatu region at São Paulo State for E. vermicularis, T. trichiura, Taenia sp., and A. lumbricoides are 3.69-10.04, 5.73-17.29, 1.22-1.62, and 6.09-10.39%, respectively (Salata et al 1972;Oliveira et al 1974;Carvalho et al 2006). Studies from other Brazilian regions have shown similar variability on the enteroparasite prevalence depending on the background of sanitary, cultural, and socioeconomic conditions (Carvalho et al 2002;Alves et al 2003;Castro et al 2004;Bencke et al 2006).…”
Section: Discussionmentioning
confidence: 91%
“…Merece destaque que até mesmo no grupo de menores de um ano foram encontrados 16 casos. 6 , em Botucatu, o grupo etário mais atingido é o de l -| 7 anos, havendo uma relação inversamente proporcional com as idades subseqüentes.…”
Section: -Giardia Lambliaunclassified
“…Observa-se que os 283 casos (23%) de Ancylostomideos aqui encontrados são valores bastante próximos àqueles de outros autores 2,3,6 , em localidades diferentes de São José do Rio Preto, respectivamente, 17,5%, 22,5% e 24%.…”
Section: -Ancylostomidae E Strongyloides Stercoralisunclassified
See 1 more Smart Citation